Model Kemitraan dalam Pemberdayaan Usaha Mikro Pedesaan. (Jurnal Ilmu Kesejahteraan Sosial, 2018)
Recent literature has explored enough strategies to empower MSMEs. This research offers a different perspective by giving more emphasis on empowerment aspects to rural business partners by student groups. The research approach used is qualitative through in-depth interviews with informants related to research questions such as students as agent of change and rural business partners. Some important findings that emerge are several strategies in empowering MSMEs that arise in partnership and foster parents models with intensive assistance from student groups to business partners. Some effective strategies found are building relationships and trust, using directive and nondirective interventions, strengths perspective, achievement motivation models and experiential learning methods. The conclusion is that the partnership model and foster parents encourage joint practices that can increase entrepreneurial capacity in developing rural micro businesses both for students and micro entrepreneurs. The recommendation from this study is that a need for balanced informations between student groups and business partners before assistance process. And also informations about empowerment for students related to knowledge, skills and values